Variation in erythromycin and clindamycin susceptibilities of Streptococcus pneumoniae by four test methods. - Fasola, E L (1997)
Susceptibilities of 124 strains of Streptococcus pneumoniae to erythromycin and clindamycin were determined by the National Committee for the Clinical Laboratory Standards (NCCLS) broth microdilution method, with incubation for 20 to 24 h in ambient air and with modifications of this method by incubation for up to 48 h in air and CO2. Strains were also tested by agar dilution, E-test, and disk diffusion; good correlation was obtained with these methods, with clear separation into bimodal populations of susceptible and resistant stains. The broth microdilution method, however, using incubation in air for 24 h (NCCLS method), misclassified 4 of 92 erythromycin-resistant strains (1 as susceptible and 3 as intermediate) and 25 of 58 clindamycin-resistant strains (all as susceptible). With the exception of one strain with clindamycin, susceptible and resistant strains were correctly classified by the microdilution method with incubation in CO2 for 24 h or in ambient air for 48 h. Disk diffusion, agar dilution, and E-test methods with incubation in 5% CO2 are therefore reliable methods for susceptibility testing of pneumococci against these agents. However, the NCCLS microdilution method, which specifies incubation for 20 to 24 h in ambient air, produced significant very major errors (43%) clindamycin. Modification of the microdilution method by incubation in 5% CO2 or by extension of incubation time in ambient air to 48 h corrected these errors. Disk diffusion, however, was shown to be a simple, convenient, and reliable method for susceptibility testing of pneumococci to erythromycin and clindamycin and is suggested as the method of choice for these agents.